The Value of Speaking for “Us”: the Relationship Between CEOs' Use of I- and We-Referencing Language and Subsequent Organizational Performance - Martin P Fladerer; S Alexander Haslam; Niklas K Steffens; Dieter Frey (Journal of Business and Psychology, 2020)
CEOs have been argued to play a critical role for organizational performance. However, CEOs cannot achieve success singlehandedly. They rely on other organizational members to execute and implement their agenda and to contribute to organizational success. In the present research, we propose that CEOs serve as identity leaders of their organization who are able to enhance organizational performance by representing and cultivating a sense of shared collective identity (“us”) with those they lead. One way for leaders to do so is through the use of we-referencing (as opposed to I-referencing) language. We examine this idea in a pre-registered study of organizations listed in the DAX (i.e., leading German stock index) between 2000 and 2016, assessing the impact of CEOs' use of we- and I-referencing language in letters to the stakeholders (N0.167em=0.167em378) on objective indicators of organizational financial performance. In line with hypotheses, results show a positive relationship between CEOs' use of we-referencing language and key indicators of financial performance: return on assets and sales per employee (while there was no evidence of an association with return on sales). At the same time, results indicate that the use of I-referencing language was unrelated to organizational performance. These findings advance the literature on strategic leadership and on the social identity approach to leadership by suggesting that CEOs' thinking and acting in collective terms is associated with greater organizational financial performance.
Keywords: 650; CEO leadership; Identity entrepreneurship; Financial performance; Social identity approach to leadership; We-referencing language; Linear mixed-modeling